Phytochemical Composition and Antimicrobial and Antibiofilm Effect of Myrciaria cauliflora Hydroethanolic Extract against Staphylococcus aureus and Acinetobacter baumannii - de Oliveira, Luciane Dias [UNESP]; Ribeiro, Ana Luisa Monteiro; Dias, Sthéfani de Oliveira [UNESP]; da Cruz, Geovani Moreira [UNESP]; de Menezes, Raquel Teles [UNESP]; de Carvalho, Lara Steffany [UNESP]; Diamantino, Mariana Gadelho Gimenez [UNESP]; Pereira, Thaís Cristine [UNESP]; Marcucci, Maria Cristina [UNESP]; Abu Hasna, Amjad [UNESP] (MDPI, 2024)
Staphylococcus aureus and Acinetobacter baumannii are opportunistic pathogens, and both are involved in different oral infections. This work aimed to analyze the phytochemical composition of Myrciaria cauliflora hydroethanolic extract and to evaluate its antimicrobial and antibiofilm action against Staphylococcus aureus (ATCC 6538) and Acinetobacter baumannii (ATCC 19606; multi-resistant clinical strains 58004, 50098, 566006, and H557). Myrciaria cauliflora hydroethanolic extract was prepared, and the content of soluble solids, flavonoids, and phenols was quantified. High-performance liquid chromatography (HPLC) was performed later. The minimum inhibitory concentration was determined using the broth microdilution method according to the Clinical and Laboratory Standards Institute, standard M7-A6, and subsequently, its minimum bactericidal concentration was determined. Then, the most effective concentrations were analyzed against biofilms. Statistical analysis was performed using the ANOVA method with Tukey’s test. The soluble solids content in the prepared hydroethanolic extract of M. cauliflora was 2.22%. Additionally, the total flavonoid content, measured using the quercetin standard curve, was 0.040 mg/mL. Furthermore, the total phenol content, determined using the gallic acid standard curve, was 0.729 mg/mL. HPLC analysis presented peaks of gallic acid (11.80 m), p-coumaric acid (12.09 m), cinnamic acid derivative (19.02 m), and ellagic acid (29.83 m). The extract demonstrated antimicrobial and antibiofilm action against all tested strains. However, the most effective antibacterial concentration against all the tested bacteria was 5.55 mg/mL. Therefore, these chemical components justify that M. cauliflora hydroethanolic extract is effective in reducing biofilm formation in S. aureus (standard strain) and A. baumannii (standard and clinical strains).
Keywords: Acinetobacter baumannii; antimicrobial and antibiofilm effect; herbal extracts; Myrciaria cauliflora; phytochemical composition; Staphylococcus aureus